A 'time bomb' in the human intestine—the multiple emergence and spread of antibiotic‐resistant bacteria. (6th November 2021) - Zhang, Yuling; Xu, Siyang; Yang, Yijun; Chou, Shan‐Ho; He, Jin
Summary: Antibiotics have a strong killing effect on bacteria and are the first choice for the prevention and treatment of bacterial infectious diseases. Therefore, they have been widely used in the medical field, animal husbandry and planting industry. However, with the massive use of antibiotics, more and more antibiotic‐resistant bacteria (ARB) have emerged. Because human intestines are rich in nutrients, have suitable temperature, and are high in bacterial abundance, they can easily become a hotbed for the spread of ARB and antibiotic‐resistant genes (ARGs). When opportunistic pathogenic bacteria in the intestine acquire ARGs, the infectious diseases caused by such opportunistic pathogens will become more difficult to treat, or even impossible to cure. Therefore, ARB in the human intestine are like a 'time bomb'. In this review, we discuss the sources of intestinal ARB and the transmission routes of ARGs in the human intestine from the perspective of One Health. Further, we describe various methods to prevent the emergence of ARB and inhibit the spread of ARGs in the human intestine. Finally, we may be able to overcome ARB in the human intestine using an interdisciplinary 'One Health' approach.